Heterogeneous C-H functionalization in water via porous covalent organic framework nanofilms: a case of catalytic sphere transmutation - Sasmal, Himadri Sekhar; Bag, Saikat; Chandra, Bittu; Majumder, Poulami; Kuiry, Himangshu; Karak, Suvendu; Sen Gupta, Sayam; Banerjee, Rahul (Journal of the American Chemical Society, 2021)
Heterogeneous catalysis in water has not been explored beyond certain advantages such as recyclability and recovery of the catalysts from the reaction medium. Moreover, poor yield, extremely low selectivity, and active catalytic site deactivation further underrate the heterogeneous catalysis in water. Considering these facts, we have designed and synthesized solution-dispersible porous covalent organic framework (COF) nanospheres. We have used their distinctive morphology and dispersibility to functionalize unactivated C-H bonds of alkanes heterogeneously with high catalytic yield (42-99%) and enhanced regioand stereoselectivity (3 degrees:2 degrees = 105:1 for adamantane). Further, the fabrication of catalyst-immobilized COF nanofilms via covalent self-assembly of catalytic COF nanospheres for the first time has become the key toward converting the catalytically inactive homogeneous catalysts into active and effective heterogeneous catalysts operating in water. This unique covalent self-assembly occurs through the protrusion of the fibers at the interface of two nanospheres, transmuting the catalytic spheres into films without any leaching of catalyst molecules. The catalyst-immobilized porous COF nanofilms' chemical functionality and hydrophobic environment stabilize the high-valent transient active oxoiron(V) intermediate in water and restricts the active catalytic site's deactivation. These COF nanofilms functionalize the unactivated C-H bonds in water with a high catalytic yield (45-99%) and with a high degree of selectivity (cis:trans = 155:1; 3 degrees:2 degrees = 257:1, for cis-1,2-dimethylcyclohexane). To establish this approach's ``practical implementation'', we conducted the catalysis inflow (TON = 424 +/- 5) using catalyst-immobilized COF nanofilms fabricated on a macroporous polymeric support.